As regras de Haia sobre arbitragem de direitos humanos e empresas (2019): um contributo para a solução de conflitos entre empresas transnacionais e vítimas de violações de direitos humanos? - Carvalho, Bruna Rabêlo (2021)
The commercial activities of transnational corporations (“TNCs”) have historically been linked with numerous human rights abuses. Damage to health caused by pollution, environmental accidents ; use of child labor; unhealthy work or working conditions similar to slavery; forced displacement of communities, such as indigenous people, to establish corporate activities; use of excessive force by private security services; discrimination against employees on the basis of race, sex or gender characteristics; financial support to authoritarian governments to make the sector’s business interests viable are only a few examples for such infringements. In view of the inadequacy of traditional monitoring mechanisms for these particular contexts and the need to address more effectively human rights violations committed by TNCs, several soft law instruments were developed in the international order. The main one are the UN Guiding Principles for Business and Human Rights, of 2011, which establish the paradigm “Protect, Respect and Remedy”, according to which the State has a duty to protect human rights in their entirety, while corporations must respect them. In addition, there must be a guarantee of reparation for possible abuses and damage caused by these actors. The present master thesis deals with arbitration as a possible mechanism of dispute resolution for redress for human rights violation committed by TNCs, shed some light on the so-called The Hague Rules on Business and Human Rights Arbitration, launched in 2019. It analyses the adequacy of this innovative instrument which pretens to fill a gap by granting a new sort of access to justice for victims of human rights violations to remedy the damage suffered. Being predominantly a bibliographic and documentary research, the dissertation addresses (i) the relationship between transnational corporations and human rights in the international scenario; (ii) arbitration as a mechanism of dispute resolution; and (iii) the Hague Rules on Business and Human Rights Arbitration (2019) as a possible instrument to be used by victims to remedy damages caused by human rights violations.